FcLDP1, a Gene Encoding a Late Embryogenesis Abundant (LEA) Domain Protein, Responds to Brassinosteroids and Abscisic Acid during the Development of Fruits in Fragaria chiloensis - Espinoza, Analía; Contreras, Rodrigo; Zúñiga, Gustavo E.; Herrera, Raúl; Moya-León, María Alejandra; Norambuena, Lorena; Handford, Michael (Frontiers in Plant Science, 2016)
White Chilean strawberries (Fragaria chiloensis) are non-climacteric fruits, with an exotic colour and aroma. In order to discover genes involved in the development of these fruits, we identified a fragment of a gene encoding a Late Embryogenesis Abundant (LEA) domain protein, FcLDP1, that was expressed in early stages of fruit development, particularly in receptacles. Hormones play key roles in regulating the development of non-climacteric fruits. We show that the brassinosteroid content of the white strawberry varies during development. Additionally, FcLDP1 as well as the closest orthologue in the woodland strawberry, F. vesca (FvLDP1) possess multiple brassinosteroid, as well as abscisic acid response motifs in the promoter region, consistent with the response of transiently-expressed FcLDP1 promoter-GFP fusions to these hormones, and the rise in FcLDP1 transcript levels in white strawberry fruits treated with brassinosteroids or abscisic acid. These findings suggest that both hormones regulate FcLDP1 expression during the development of white strawberries.